2010
DOI: 10.1371/journal.pone.0009556
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Cronobacter sakazakii BAA-894 and Comparative Genomic Hybridization Analysis with Other Cronobacter Species

Abstract: BackgroundThe genus Cronobacter (formerly called Enterobacter sakazakii) is composed of five species; C. sakazakii, C. malonaticus, C. turicensis, C. muytjensii, and C. dublinensis. The genus includes opportunistic human pathogens, and the first three species have been associated with neonatal infections. The most severe diseases are caused in neonates and include fatal necrotizing enterocolitis and meningitis. The genetic basis of the diversity within the genus is unknown, and few virulence traits have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
214
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(229 citation statements)
references
References 58 publications
9
214
1
Order By: Relevance
“…The reclassification scheme described by Iversen et al (2007Iversen et al ( , 2008a was supported subsequently by both optical mapping and genome sequencing data, which confirmed the revision of the taxonomic positions of the seven species (Yan et al, 2012;Kotewicz & Tall, 2009;Kucerova et al, 2010;Stephan et al, 2011;Joseph et al, 2012;Grim et al, 2013). Although C. sakazakii and C. malonaticus were found to be closely related and difficult to distinguish by 16S rDNA gene sequence analysis, a MLST scheme reported by Baldwin et al (2009) was shown to support the separation of these two species (Yan et al, 2012).…”
Section: Molecular Characterization Of Strainssupporting
confidence: 54%
See 4 more Smart Citations
“…The reclassification scheme described by Iversen et al (2007Iversen et al ( , 2008a was supported subsequently by both optical mapping and genome sequencing data, which confirmed the revision of the taxonomic positions of the seven species (Yan et al, 2012;Kotewicz & Tall, 2009;Kucerova et al, 2010;Stephan et al, 2011;Joseph et al, 2012;Grim et al, 2013). Although C. sakazakii and C. malonaticus were found to be closely related and difficult to distinguish by 16S rDNA gene sequence analysis, a MLST scheme reported by Baldwin et al (2009) was shown to support the separation of these two species (Yan et al, 2012).…”
Section: Molecular Characterization Of Strainssupporting
confidence: 54%
“…They reported that neither mannose-sensitive type 1 fimbriae nor type 3 fimbriae were involved in the adhesion of Cronobacter to the cells. Comparatively, one striking difference among Cronobacter as reported by Kucerova et al (2010), Jospeh & Forsythe (2011) and Stephan et al (2011) is the finding that C. sakazakii does not possess the genes encoding curli, whereas C. turicensis does. However, the implications of these findings in virulence have not been fully studied.…”
Section: Attachment and Invasionmentioning
confidence: 90%
See 3 more Smart Citations